Towards Personalized 3D Augmented Reality Windshield Displays in the Context of Automated Driving - Riegler, Andreas; Riener, Andreas; Holzmann, Clemens (Frontiers in Future Transportation, 2022)
As vehicle automation advances, drivers of automated vehicles become more disengaged from the primary driving task. Windshield displays provide a large screen space supporting drivers in non-driving related activities. This article presents user preferences as well as task and safety issues for 3D augmented reality windshield displays in automated driving. Participants of a user study (n = 24) customized two modes of content presentation (multiple content-specific windows vs. one main window), and could freely adjust visual parameters for these content windows using a simulated “ideal” windshield display in a virtual reality driving simulator. We found that user preferences differ with respect to contextual aspects. Additionally, using one main content window resulted in better task performance and lower take-over times, but the subjective user experience was higher for the multi-window user interface. These findings help automotive interface designers to improve experiences in automated vehicles.